IMPROVING STUDENTS’ NARRATIVE WRITING THROUGH BLOOKET-BASED LEARNING - Diana Az-Zahra Mulyana; Irsyad Nugraha; Wahid Hasim (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
This research is motivated by the low narrative writing skills of English as a Foreign Language (EFL) students due to low motivation and the use of less interactive learning methods. The focus of this research problem is directed at testing the effectiveness of the Blooket digital platform as a game-based learning medium to optimize the ability to compose narrative texts. This quantitative study applies a quasi-experimental method with a non-equivalent control group design involving the experimental class and the control class at the junior high school level in Garut. The research procedure begins with a pre-test, implementation of an intervention in the form of integrating the Blooket interactive questionnaire for four meetings, and ends with a writing post-test. The results of quantitative data analysis using the SPSS program show a significant increase in the average score of the experimental class from 61.94 to 80.83 with a gain score of 18.89 and a significance value of p = 0.000 less than 0.05. In contrast, the control class did not show significant progress. The main conclusion confirms that the integration of Blooket is proven to be effective in significantly boosting students' writing skills. In addition to the academic aspects, the use of game elements has successfully fostered motivation, active participation, and students' self-confidence in organizing story ideas in a coherent and enjoyable manner during the learning process. ABSTRAK Penelitian ini dilatarbelakangi oleh rendahnya keterampilan menulis teks naratif pada siswa kelas English as a Foreign Language (EFL) akibat rendahnya motivasi serta penggunaan metode pembelajaran yang kurang interaktif. Fokus masalah dalam riset ini diarahkan pada pengujian efektivitas platform digital Blooket sebagai media pembelajaran berbasis gim untuk mengoptimalkan kemampuan menyusun teks naratif. Studi kuantitatif ini menerapkan metode eksperimen semu dengan desain non-equivalent control group yang melibatkan kelas eksperimen dan kelas kontrol pada jenjang sekolah menengah pertama di Garut. Prosedur penelitian diawali dengan pemberian pra-tes, pelaksanaan intervensi berupa pengintegrasian kuesioner interaktif Blooket selama empat pertemuan, dan diakhiri dengan pemberian pasca-tes menulis. Hasil analisis data kuantitatif menggunakan bantuan program SPSS menunjukkan peningkatan nilai rata-rata kelas eksperimen secara signifikan dari 61,94 menjadi 80,83 dengan capaian skor gain sebesar 18,89 serta nilai signifikansi p = 0,000 kurang dari 0,05. Sebaliknya, kelas kontrol tidak memperlihatkan kemajuan yang berarti. Simpulan utama menegaskan bahwa integrasi Blooket terbukti efektif dalam mendongkrak keterampilan menulis siswa secara nyata. Selain aspek akademis, pemanfaatan elemen gim ini sukses menumbuhkan motivasi, partisipasi aktif, serta rasa percaya diri siswa dalam mengorganisasikan ide cerita secara koheren dan menyenangkan selama proses pembelajaran.